2019
DOI: 10.31788/rjc.2019.1245469
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Interactions in Binary Liquid Mixtures Containing Benzyl Benzoate

Abstract: Speeds of sound, densities and viscosities of the binary mixture of Benzyl benzoate with mole fractions of amides -Formamide (FA), N-Methyl formamide (NMF) and Di methyl formamide (DMF) have been estimated utilizing the standard strategies at 303.15, 308.15 and 313.15K. From these deliberate values, different thermo-dynamic parameters such as isentropic compressibility (K s ), intermolecular free length (L f ), molar volume (V m ), Gibbs free energy (∆G), enthalpy (H) and their excess properties were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Several workers [28][29][30] reported that negative excess volumes indicate strong interactions between the components of mixtures. The VE values become more and more negative 31,32 as the temperature is increased from 303.15K to 318.15K. This indicates that as the temperature increases the inter hydrogen bond in the associated salicylates become weaker and dipole.…”
Section: Benzyl Salicylatementioning
confidence: 94%
“…Several workers [28][29][30] reported that negative excess volumes indicate strong interactions between the components of mixtures. The VE values become more and more negative 31,32 as the temperature is increased from 303.15K to 318.15K. This indicates that as the temperature increases the inter hydrogen bond in the associated salicylates become weaker and dipole.…”
Section: Benzyl Salicylatementioning
confidence: 94%